Sodium Butyrate Abrogates the Growth and Pathogenesis of Mycobacterium bovis via Regulation of Cathelicidin (LL37) Expression and NF-κB Signaling - Zhang, Kai; Hussain, Tariq; Wang, Jie; Li, Mengying; Wang, Wenjia; Ma, Xiaojing; Liao, Yi; Yao, Jiao; Song, Yinjuan; Liang, Zhengmin; Zhou, Xiangmei; Xu, Lihua (Frontiers in Microbiology, 2020)
Mycobacterium bovis (M. bovis) is the causative agent of bovine tuberculosis, has been identified a serious threat to human population. It has been found that sodium butyrate (NaB), the inhibitor of histone deacetylase, can promote the expression of cathelicidin (LL37) and help the body to resist a variety of injuries. In the current study, we investigate the therapeutic effect of NaB on the regulation of host defense mechanism against M. bovis infection. We found an increased expression of LL37 in M. bovis infected THP-1 cells after NaB treatment. In contrast, NaB treatment significantly down-regulated the expression of Class I HDAC in THP-1 cells infected with M. bovis. Additionally, NaB reduced the expression of p-P65 and p-IkBa, indicating the inhibition of Nuclear Factor-κB (NF-κB) signaling. Furthermore, we found that NaB treatment reduced the production of inflammatory cytokines (IL-1Bb, TNF-α αand IL-10) and a key anti-apoptotic marker protein Bcl-2 in THP-1 cell infected with M. bovis. Notably, mice showed high resistancet to M. bovis infection after NaB treatment. The reduction of viable M. bovis bacilli indicates that NaB-induced inhibition of M. bovis infection mediated by upregulation of LL37 and inhibition of Nuclear Factor-κB (NF-κB) signaling pathway. These observations illustrate that NaB mediate protective immune responses against M. bovis infection. Overall, these results suggest that NaB can be exploited as a therapeutic strategyremedy for the control of M. bovisne in animals and human beings.